Sistem Informasi Pelayanan Administrasi Kependudukan Kelurahan Kenteng Berbasis Website dengan Uji Kualitas Sistem Menggunakan Metode Mccall Software Quality - Wahyu Eka Mulatsari; Diwahana Mutiara Candrasari; Suyudi Suyudi (Universitas Ivet, 2023)
Kenteng Village provides population administration services to the community by means of residents coming to the village and village officials processing administrative applications needed by residents and residents taking printed letters. This is not considered effective and efficient because in making the letter, residents still have to wait to take the letter. Therefore, it is necessary to build a website-based population administration service information system for the Kenteng sub-district that can assist the service process effectively and efficiently. This system is built using the codeignter framework and the system development method using Prototype. The websitebased population administration service information system sub-district was tested for quality using the McCall Software quality method and overall quality was produced in a good category with an overall percentage of 62.18% which included the Correctness factor with a percentage of 69%, Reliability with a percentage of 76.75%, Efficiency with a percentage of 89.25%, Integrity with a percentage of 71%, Usability with a percentage of 70%, Maintainability with a percentage of 52.35%, Flexibility with a percentage of 50.25%, Testability with a percentage of 69%, Portability with a percentage of 66%, Reusability with a percentage percentage of 51% and Interoperability with a percentage of 67%.